Tissue‐specific roles of FGF signaling in external genitalia development. Issue 6 (June 2015) - Harada, Masayo; Omori, Akiko; Nakahara, Chiaki; Nakagata, Naomi; Akita, Keiichi; Yamada, Gen
Abstract : Background: The developmental processes of the genital tubercle (GT), the anlage of the external genitalia, possess several developmental aspects, including GT outgrowth, urethral tube formation, and epithelial differentiation of the urethra. The GT comprises the mesenchyme derived from the lateral mesoderm, ectodermal epithelium, and endodermal epithelium (embryonic urethral epithelium). The three tissue layers develop the GT coordinately.Results: Around the initial stage of GT outgrowth (E11.5), FGF signaling was detected in the mesenchyme of the GT. FGF signaling was detected in the three tissue layers of the GT around the early stage of urethral formation (E13.5). Subsequently, FGF signaling was predominantly detected in the urethral epithelium (E14.5). Tissue‐specific roles of FGF signaling in GT development were revealed by conditional Fgfr gene knockout approaches. Mesenchymal FGF signaling in the early‐stage GT is required for its outgrowth. Ectodermal FGF signaling in the GT is required for the differentiation of the ectoderm and urethral epithelium at their junction to form the proper urethral tube. Endodermal FGF signaling in the GT is required for the stratification and cell adhesive characteristics of the urethral epithelium.Conclusions: The current study suggests that spatiotemporally regulated FGF signaling plays tissue‐specific roles in multiple processes of external genitalia development. Developmental Dynamics 244:759–773, 2015 . © 2015 Wiley Periodicals, Inc. Key Findings: FGF signaling was detected in the three tissue layers of the genital tubercle (GT), the anlage of the external genitalia. The region and intensity of FGF signaling was dynamically altered during GT development. Mesenchymal FGF signaling in the early‐stage GT is required for GT outgrowth. Ectodermal FGF signaling is required for urethral tube formation. Endodermal FGF signaling is required for the stratification and adhesive characteristics of the urethral epithelium.